Ethical Financing and Sustainability Practices in Islamic Banking Institutions - Rasnawati Rasnawati; Wahyuddin Abdullah; Sumarlin Sumarlin (Universitas Muhammadiyah Makassar, 2025)
This study examines the integration of sustainability and ethical financing principles in Islamic banking institutions and their implications for financial performance, corporate reputation, and customer trust. Despite increasing global attention to sustainable finance, there remains limited understanding of how Islamic banks adopt and operationalize sustainability practices while addressing challenges such as regulatory constraints, resource limitations, and market competition. Adopting an interpretive paradigm and a case study approach, this research collected data through in-depth interviews with institutional managers and staff, complemented by document analysis of sustainability reports and policy guidelines. The results reveal that Islamic banks that actively implement sustainability and ethical financing practices demonstrate improved profitability, enhanced corporate reputation, and greater customer loyalty. Moreover, transparent sustainability reporting and accountability mechanisms strengthen stakeholder trust and align institutional practices with the broader objectives of Islamic finance, such as social justice and environmental stewardship. The findings highlight the importance of developing innovative Sharia-compliant products that integrate sustainability values to attract socially and environmentally conscious customers. From a theoretical perspective, the study contributes to the growing discourse on the intersection between Islamic finance and sustainable development. Practically, it provides implications for policymakers and practitioners to strengthen transparency, accountability, and innovation in Islamic banking operations. Future research is recommended to explore the role of emerging technologies, including fintech and digital platforms, in enhancing sustainability practices within the Islamic banking sector.